The Dancer Within : Intimate Conversations with Great Dancers - Eichenbaum, Rose (Book collections on Project MUSE., 2008)
"The Dancer Within is a collection of photographic portraits and short essays based on confessional interviews with forty dancers and entertainers, many of them world famous. Well-known on the concert stage, Broadway, in Hollywood musicals, and on television, the personalities featured in this book speak with extraordinary candor about all stages of the dancer's life - from their first dance class to their signature performances and their days of reflection on the artist's life. The Dancer Within reveals how these artists triumphed, but also how they overcame adversity, including self-doubt, injuries, and aging. Most of all, this book is about the courage, commitment, love, and passion of these performers in their quest for artistic excellence. The reader will quickly realize that "the dancer within" is a metaphor of the human spirit."--Jacket